The Effect Of Work Culture And Self-Efficacy On Employee Performance - Syafira Zatil Aqmar (At-Tadbir : jurnal ilmiah manajemen, 2022)
The success of a company is directly related to the success of its employees. Employees that excel can take the company to the next level. Quality, quantity, efficiency, and effectiveness, as well as the ability to work together with others, are all important components of a successful individual performance standard set by an organization. Workplace culture and employee self-efficacy were examined to see how they affected productivity. This study relies on a quantitative verification method to gather its data. The instrument of choice was a questionnaire. KJP Sugianto Prasodjo has a total workforce of 174 people. 100 employees were chosen at random for the study's sample (random sampling). The data was analyzed with Smart PLS 3.0. There was a significant relationship between work culture and employee performance (p<0.05), as well as between employee self-efficacy and work culture (p<0.05), as well as between these three variables (p<0.05). An improved work culture model is likely to be developed as a result of further research